2020
DOI: 10.1177/0194599820965236
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Normal and Abnormal Tympanogram Findings in Eustachian Tube Dysfunction

Abstract: Objective To characterize the relationship between objective tympanogram values and patient-reported symptoms and associations with common comorbid conditions. Study Design Cross-sectional study with prospective data collection. Setting Tertiary medical center. Methods Patients undergoing routine audiometric evaluation between October 2018 and June 2019 were included. Participants with temporomandibular joint dysfunction, inner ear hydrops, and similar conditions were excluded. Symptoms were assessed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…Symptoms such as ear pain, fullness, and popping may present with a number of conditions such as migraine, 40 superior semicircular canal dehiscence, Meniere's disease, temporomandibular disorders (TMJ), 41 sinus disease, sore throat, or dental pain that may be unrelated to Eustachian tube function. McCoul et al suggested that the presence of normal tympanometry with positive ETDQ‐7 scores may be due to insensitivity of the currently accepted interpretation standards for tympanometry 42 . It is an important point that objective measures of Eustachian tube function such as otoscopy, tympanometry, or tubomanometry are imperfect measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms such as ear pain, fullness, and popping may present with a number of conditions such as migraine, 40 superior semicircular canal dehiscence, Meniere's disease, temporomandibular disorders (TMJ), 41 sinus disease, sore throat, or dental pain that may be unrelated to Eustachian tube function. McCoul et al suggested that the presence of normal tympanometry with positive ETDQ‐7 scores may be due to insensitivity of the currently accepted interpretation standards for tympanometry 42 . It is an important point that objective measures of Eustachian tube function such as otoscopy, tympanometry, or tubomanometry are imperfect measures.…”
Section: Discussionmentioning
confidence: 99%
“…McCoul et al suggested that the presence of normal tympanometry with positive ETDQ‐7 scores may be due to insensitivity of the currently accepted interpretation standards for tympanometry. 42 It is an important point that objective measures of Eustachian tube function such as otoscopy, tympanometry, or tubomanometry are imperfect measures. However, given the number of conditions that may cause the relatively nonspecific symptoms of OETD and how hard it can be to exclude certain conditions, such as TMJ, objective measures of OETD such as tympanometry will always remain critical for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the historic criterion of an abnormal tympanogram for diagnosis of ETD may be further refined to reflect the potential for varying degrees of obstructive ETD among patients with type A tympanograms. 19 Statistically and clinically significant improvements were noted in the WPAI and SNOT-22 scores after BDET. The WPAI is a validated measure of work impairment, 15 and in our population, statistically significant improvements were seen in the presenteeism, productivity loss, and activity impairment components of the WPAI at both…”
Section: Discussionmentioning
confidence: 86%
“…8 Some patients may present with symptoms of ETD yet have normal otologic exams and tympanometry, which highlights the need for additional diagnostic tools. 9 Other conditions like temporomandibular joint disorder and endolymphatic hydrops can manifest similar symptoms, which can make accurate diagnosis a challenge. 10 Although there exist several objective tests of ET function such as tubomanometry and sonotubometry, none are readily available nor practical for clinical use by most otolaryngologists.…”
mentioning
confidence: 99%
“…Although the diagnostic evaluation of ETD continues to evolve, it has conventionally been multimodal with contributions from history and physical examination (including pneumatic otoscopy), nasal endoscopy, and audiometry with tympanometry 8 . Some patients may present with symptoms of ETD yet have normal otologic exams and tympanometry, which highlights the need for additional diagnostic tools 9 . Other conditions like temporomandibular joint disorder and endolymphatic hydrops can manifest similar symptoms, which can make accurate diagnosis a challenge 10 .…”
mentioning
confidence: 99%